Research on schedulability analysis algorithm of airborne multi partition system - ZHANG Min; WU Junsheng; CUI Xining; SUN Jingchang (Xibei Gongye Daxue Xuebao, 2023)
Partition operating system conforming to ARINC653 is widely used in airborne to support application software integration. Under the two-level scheduling model for partition operating system, the demanding real-time requirements of airborne software are usually difficult to obtain effective deterministic guarantee, so it is very important to analyze the schedulability of the system. Judging whether the scheduling table can meet the real-time requirements of the process in the partition through the schedulability analysis algorithm is an effective means to ensure that all processes in the system complete the computing task within the specified time. Based on the method of operations research and the introduction of virtual process, a schedulability analysis algorithm for multi partition system is designed, and the numerical verification is carried out. The verification results show that the algorithm can accurately judge whether the scheduling table matches the process time attribute, give the qualitative analysis conclusion of whether the system can be scheduled, help the system integrator to verify the rationality of the scheduling table before the actual operation of the system, and reduce the risk of test and flight test.